2021
DOI: 10.1111/jonm.13244
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers' perceived level of collaboration with hospital nurses: A cross‐sectional study

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Advancing the quality of health care means, in the logic of complexity thinking, welcoming and apprehending the mother caregiver in her uniqueness and complementarity, as well as transcending linear perceptions and achieving an integrated, collaborative and inseparable dynamic between theoretical knowledge and lived knowledge ( 28 ) . This evolution, which does not exclude disorder, implies recognizing that the quality of care is associated with the ability to evolve in the inseparability and dialogicity between the notions of order and disorder, with a view to (re)organization.…”
Section: Discussionmentioning
confidence: 99%
“…Advancing the quality of health care means, in the logic of complexity thinking, welcoming and apprehending the mother caregiver in her uniqueness and complementarity, as well as transcending linear perceptions and achieving an integrated, collaborative and inseparable dynamic between theoretical knowledge and lived knowledge ( 28 ) . This evolution, which does not exclude disorder, implies recognizing that the quality of care is associated with the ability to evolve in the inseparability and dialogicity between the notions of order and disorder, with a view to (re)organization.…”
Section: Discussionmentioning
confidence: 99%
“…Family members also reported not having enough opportunities to participate in care planning, aligning with a similar result that had been discovered earlier [ 14 ]. This may be due to limited contact with nurses, which makes it difficult to participate in care planning [ 35 ]. Perceptions of care quality have previously been shown to depend strongly on having clear information about the next step in care and follow-up [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FCS was a 56-item scale before being revised by Lindhardt and colleagues [ 21 ]. Parallel to the Danish FCS is a version in Dutch revised as a 20-item scale, narrowing the focus and including only items on collaboration, evaluated using face and content validity [ 22 , 23 ]. In addition, the sample in the study based on the Norwegian version of the FCS was smaller (n = 147), with many drop-outs (34%), and the psychometric methods were different [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using the FCS have shown that family caregiver characteristics such as age and cohabitation with the patient are positively associated with the perception of better collaboration. In addition, a higher frequency of contact with nurses was associated with the perception of better collaboration [ 22 ]. There are validated versions of the FCS in Dutch [ 23 ] and Norwegian [ 24 ], but there is as yet none in Swedish.…”
Section: Introductionmentioning
confidence: 99%